Jump rope training effects on health- and sport-related physical fitness in young participants: A systematic review with meta-analysis. Issue 16 (18th August 2022) - Singh, Utkarsh; Ramachandran, Akhilesh Kumar; Ramirez-Campillo, Rodrigo; Perez-Castilla, Alejandro; Afonso, José; Manuel Clemente, Filipe; Oliver, Jon
ABSTRACT: The aim of this systematic review with meta-analysis was to assess the available body of published peer-reviewed articles related on the effects of jump rope training (JRT) compared with active/passive controls on health- and sport-related physical fitness outcomes. Searches were conducted in three databases, including studies that satisfied the following criteria: i) healthy participants; ii) a JRT programprogramme; iii) active or traditional control group; iv) at least one measure related to health- and sport-related physical fitness; v) multi-arm trials. The random-effects model was used for the meta-analyses. Twenty-one moderate-high quality (i.e., PEDro scale) studies were meta-analysed, involving 1, 021 participants (male, 50.4%). Eighteen studies included participants with a mean age <18 years old. The duration of the JRT interventions ranged from 6 to 40 weeks. Meta-analyses revealed improvements (i.e., p = 0.048 to <0.001; ES = 0.23–1.19; I 2  = 0.0–76.9%) in resting heart rate, body mass index, fat mass, cardiorespiratory endurance, lower- and upper-body maximal strength, jumping, range of motion, and sprinting. No significant JRT effects were noted for systolic-diastolic blood pressure, waist-hip circumference, bone or lean mass, or muscle endurance. In conclusion, JRT, when compared to active and passive controls, provides a range of small-moderate benefits that span health- and sport-related physical fitness outcomes.